Cable-driven underactuated wearable robotic devices for hand assistance - Bernardo, Alexandre Pinto Sales de Noronha (Nanyang Technological University, 2023)
Wearable robots have shown promise for providing high-intensity, repetitive training in post-stroke rehabilitation settings, but also for aiding in performing activities of daily life. Most current robotic solutions make use of either rigid or soft mechanisms. The former can provide more power with accurate control at the cost of bulkiness with the risk of joint misalignment. These are generally more convenient for use in a clinical scenario, especially due to the need for a grounded, stationary system. The latter are typically lighter and more adaptable, but more difficult to control in a precise manner, particularly at the joint level. However, due to their light weight, they are feasible for applications which require a portable system. A hybrid approach, where rigid and soft elements are used in tandem, combine the advantages of both soft and rigid mechanisms and have come into prominence in recent years. They have the potential of delivering precise control in a lightweight implementation, increasing their wearability. Nevertheless, there is still a shortage of available solutions illustrating the capacities of a hybrid approach.